Adaptive reorganization of 2D molecular nanoporous network induced by coadsorbed guest molecule - Zheng, Qing-Na (Langmuir : the ACS journal of surfaces and colloids, 2014)
The ordered array of nanovoids in nanoporous networks, such as honeycomb, Kagome, and square, provides a molecular template for the accommodation of "guest molecules". Compared with the commonly studied guest molecules featuring high symmetry evenly incorporated into the template, guest molecules featuring lower symmetry are rare to report. Herein, we report the formation of a distinct patterned superlattice of guest molecules by selective trapping of guest molecules into the honeycomb network of trimesic acid (TMA). Two distinct surface patterns have been achieved by the guest inclusion induced adaptive reconstruction of a 2D molecular nanoporous network. The honeycomb networks can synergetically tune the arrangement upon inclusion of the guest molecules with different core size but similar peripherals groups, resulting in a trihexagonal Kagome or triangular patterns